Mamoura forest between the problem of climate change, human pressure and ways to adapt (Morocco) - Benaissa, Hanane; Sadik, Abdnour; Bahou, Abdelaziz (Journal of Humanities & Social Sciences, 2022)
The Moroccan forests are characterized by *the plurality of ecosystems, and a remarkable biological diversity, represented by about (4,000) plant species, (550) vertebrates and (1,000) other animal species. Forest systems play several functions, including combating desertification, preserving biodiversity and structuring the natural space. Environmental imbalances under human pressure and the repercussions of climate change require placing the forest sector at the heart of the country’s sustainable development projects. The Mamoura forest is considered a national heritage of great importance in Morocco, and is known as one of the largest cork oak forests in the world, which represents about (150,000) hectares of an area of (300,000) hectares scattered in the rest of the countries of the Mediterranean basin. In spite of the privileges that the forest of the globe is characterised with, it suffers from a significant deterioration in forest formations and ecosystems. *In fact, this deterioration was not a result of the moment; rather,* it goes back to the ancient historical periods which were controlled by a number of natural and human factors either due to the random and intensive grazing or the excessive exploitation of forest resources by the inhabitants of the region. * the decline in rain precipitation and the rise in temperature, in addition to biological diseases, which indicates that it is in an inappropriate position to ensure its continuity. *Consequently, this prompted the State with the help of institutions, through enacting new strategies and plans with the participation of *the* civil society represented in many associations and cooperatives. The aim of this initiative was to brationalize the exploitation of forest resources without compromising their sustainability, and to adapt to climatic changes that are affecting the forest all over the world.